The Design and Development of Motion Graphics Media for Schizophrenia Education - พีรกรวรธรรม, ปภัชญา; ศิริวรรณ์, นัฐวุฒิ; ดีเจริญชิตพงศ์, จิรวิญญ์; เขื่อนแก้ว, ปรานต์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This study aimed to 1) design and develop motion graphic media to provide knowledge about schizophrenia, 2) evaluate the quality of the media by experts, 3) study schizophrenia and individuals currently affected by the disorder, and 4) disseminate information to enhance public understanding of people with schizophrenia in terms of causes, symptoms, and treatment, with the research sample consisting of 30 people who use social media in Bangkok, data analyzed using percentage statistics, and motion graphic video clips and questionnaires employed as research instruments, and the results revealed that most of the participants were female, accounting for 60%, were aged between 20-25 years, accounting for 63.3%, had a high overall level of awareness or familiarity with the term schizophrenia, with the highest proportion having heard of the disease in passing at 70%, and that most participants had no direct experience with individuals with schizophrenia, accounting for 60%, while the motion graphic media developed to provide knowledge about schizophrenia received a good level of satisfaction from content experts (= 4.21, S.D. = 0.42), a good level of satisfaction from motion graphic design experts (= 4.09, S.D. = 0.84), and a good level of satisfaction from the general population (= 4.20, S.D. = 0.70).